2014
DOI: 10.3389/fimmu.2014.00153
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Liquid Self: How Time, Geography, and Life Experiences Reshape the Biological Identity

Abstract: The conceptualization of immunological self is amongst the most important theories of modern biology, representing a sort of theoretical guideline for experimental immunologists, in order to understand how host constituents are ignored by the immune system (IS). A consistent advancement in this field has been represented by the danger/damage theory and its subsequent refinements, which at present represents the most comprehensive conceptualization of immunological self. Here, we present the new hypothesis of “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 165 publications
(209 reference statements)
3
41
0
Order By: Relevance
“…In Zvi Grossman's horizontal networks (30) "the relative probability of maturation increases with antigen dose and with affinity" and "proliferation can be uncoupled from differentiation under certain predictable conditions", which are key assumptions in our model as well. Grignolio et al recently compiled factors that potentially influence immunological identity, focusing on the changing nature of immunological self, which they conceptualize as "liquid self" (31). The concept of immunological homunculus by Irun Cohen et al (32) states that non-reactivity can only create chaos, self-reactivity is required for control and order.…”
Section: Discussionmentioning
confidence: 99%
“…In Zvi Grossman's horizontal networks (30) "the relative probability of maturation increases with antigen dose and with affinity" and "proliferation can be uncoupled from differentiation under certain predictable conditions", which are key assumptions in our model as well. Grignolio et al recently compiled factors that potentially influence immunological identity, focusing on the changing nature of immunological self, which they conceptualize as "liquid self" (31). The concept of immunological homunculus by Irun Cohen et al (32) states that non-reactivity can only create chaos, self-reactivity is required for control and order.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31–32 ] Even our immunological “languaging” does not well characterize homeostasis between host endogenous and exogenous microbial flora. [ 33–34 ] What distinguishes a commensal organism from a pathogen remains a murky question: for example, many organisms, such as Neisseria meningitidis or Streptococcus pneumoniae , are able to switch between commensal and pathogenic behaviors. [ 35–37 ] An improved understanding of immune tolerance may lead to insights into infectious disease pathophysiology, particularly for M. tuberculosis .…”
Section: Evolutionary Perspectives On Immune Tolerance To Tuberculosismentioning
confidence: 99%
“…The cells of the IS are not only able to recognize external and internal stressors but also to adapt and modify according to the variety of stimuli they are exposed to, this basic characteristic of the IS as a whole is known as plasticity 286 . For this reason, it has been suggested that together with the type of molecular stimuli and their doses also the temporal sequence is critical.…”
Section: Potential Future Developments: the Context Dimensionmentioning
confidence: 99%
“… Liquid self: According to Grignolio et al 286 , the full integration of the immune response mechanisms into the host body's ecosystems, i.e., in adding the temporal, as well as the geographical/evolutionary and environmental dimensions.…”
mentioning
confidence: 99%